Impact of a Community-Based Healthy Lifestyle Program on Individuals With Traumatic Brain Injury. Issue 6 (November 2018) - Driver, Simon; Reynolds, Megan; Woolsey, Anne; Callender, Librada; Prajapati, Purvi K.; Bennett, Monica; Kramer, Kaye
Abstract : Objectives: To examine adherence with and effect of an evidence-based healthy lifestyle intervention modified for individuals with traumatic brain injury (TBI). Design: Pre-/postintervention without control. Setting: Community. Participants: Eighteen individuals with TBI: primarily male (61%), white (67%), with private insurance (50%). Mean age was 45.6 ± 12.3 years, weight 210 ± 42.6 lb, and body mass index 31.8 ± 4.6 (obese category) at baseline. Interventions: The primary goal of the Diabetes Prevention Program Group Lifestyle Balance program is 5% to 7% weight loss through increased physical activity and improved dietary behaviors. Main Outcome Measure(s): Adherence (ie, session attendance and self-monitoring of dietary behaviors), physiologic changes (ie, weight loss, blood pressure; waist and arm circumference; and lipid profile), and quality of life (ie, self-reported health, quality of life, and step count). Results: Average participant attendance (85% over 12 months) and self-monitoring (90% over 6 months) were high. Significant decreases were observed in diastolic blood pressure and waist and arm circumference from baseline through 12 months and from baseline to 3 months only for weight and total cholesterol. No significant changes were observed in self-reported health, quality of life, or step count. Conclusions: Participants demonstrated high adherence with the program, suggesting that individuals with TBI are able to successfully engage in the program and achieve significant weight loss and changes in key physiologic outcomes.